(untitled) (Vietnam Journal of Community Medicine, 2025)
Summary: Kidney cancer is a less common type of cancer and has a better prognosis than many other types of cancer. Kidney cancer has many different types of histopathology but renal cell carcinoma (RCC) accounts for 90% of kidney cancer cases. Pazopanib has been approved for the first-line treatment of metastatic renal cell carcinoma. Objectives: describe the initial clinical and imaging responses, follow-up the progression-free survival (PFS) and common side effects of pazopanib. Methods: report a case of metastatic RCC treated in the first line with pazopanib. Results: the patient got a partial response after 6 months of pazopanib treatment, and stable disease after 29 months of the treatment. Side effects when taking the drug include fatigue, hypertension, and diarrhea. Side effects were controlled without having to adjust the pazopanib dose. Conclusion: pazopanib is a targeted drug with high effectiveness, long disease-free survival, and safety in first-line treatment of patients with metastatic RCC.